2019
DOI: 10.1111/sji.12752
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated Rac1 promotes apoptosis and inhibits the clearance of apoptotic cells in airway epithelial cells, which may be associated with airway hyper‐responsiveness in asthma

Abstract: The accumulation of airway apoptotic cells may be an important factor causing airway hyper-responsiveness (AHR). Whether the apoptotic cells can be promptly removed is related to the occurrence and course of asthma. In recent years, studies have shown that Rac1 is involved in many cellular biological activities including the formation and elimination of apoptotic cells. In this study, based on the analysis of airway local cells and related factors in asthmatic mice, we evaluated the expression of Rac1 in airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Apoptosis is a form of programmed cell death that plays an essential role in lung disease, such as asthma. Elevated levels of apoptosis in bronchial epithelial cells have been reported in patients with childhood asthma 40,41 . Therefore, it is important to investigate the potential mechanism of apoptosis in asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis is a form of programmed cell death that plays an essential role in lung disease, such as asthma. Elevated levels of apoptosis in bronchial epithelial cells have been reported in patients with childhood asthma 40,41 . Therefore, it is important to investigate the potential mechanism of apoptosis in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of apoptosis in bronchial epithelial cells have been reported in patients with childhood asthma. 40,41 Therefore, it is important to investigate the potential mechanism of apoptosis in asthma. Some studies have reported that Fbp1 can promote apoptosis in certain cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ARHGAP24 significantly inhibits the activities of RhoA and Rac1 and induced apoptosis of lung cancer cells via STAT6-WWP2-p27 axis (74). Rac1 participates in the formation and elimination of apoptotic cells and coordinates receptor signals related to apoptosis and proliferation (75,76). In B-cell lymphoma, Rac1 was found to be a new binding partner of Bcl-2, which can stabilize its antiapoptosis activity (77).…”
Section: Rac1 Participates In the Cell Cycle Apoptosis And Proliferationmentioning
confidence: 99%
“…[24][25][26][27] Through immunofluorescence staining, Jiangbo Wang et al discovered that the expression of caspase-3 in bronchial epithelial cells of asthma patients increased, and the increase was most evident in samples from patients with severe asthma. 28 Increased apoptosis of airway epithelial cells was also found in asthma mice influenced by OVA, 29 HDM, 30 and the fungal allergen Alternaria alternata. 31 Studies have shown that the increased apoptosis of epithelial cells is a crucial mechanism by which some external factors cause the worsening of asthma.…”
Section: Apoptosis In Asthmamentioning
confidence: 95%